Computer-supported peer commenting: a promising instructional method to promote skill development in vocational education - Gavota, Monica Cristiana [Verfasser]; Cattaneo, Alberto [Verfasser]; Arn, Christoph [Verfasser]; Boldrini, Elena [Verfasser]; Motta, Elisa [Verfasser]; Schneider, Daniel [Verfasser]; Betrancourt, Mireille [Verfasser] (My University, 2010)
"In vocational education, a challenging issue is to help apprentices build integrated knowledge from workplace training and school teaching. The present research proposes a learning design in which apprentices are required to write with a reciprocal peer-tutoring approach about situations they encountered in the workplace in order to help in building such articulation. Two studies were conducted in order to investigate the effect of peer-commenting learning designs that were elaborated in close collaboration with teachers, on the basis of both theoretical assumptions and field specificities. The findings showed that in both studies, apprentices were able to provide useful comments, corrections and revisions to their peers' entries and that the productions significantly improved as a result of these interventions. Furthermore, apprentices found the writing activity useful for learning and enjoyable. These studies provided insightful information regarding the implementation of computer-supported writing activities that can actually foster professional skill acquisition and development. Moreover, they illustrate a concrete learning design that could be adapted to any vocational education level and subject matter." (Autorenreferat, BIBB-Doku)

Die in diesem Artikel vorgestellten Forschungsergebnisse beziehen sich überwiegend auf das Projekt "Dual-T". Im Mittelpunkt dieses Projektes steht die Frage, wie Informations- und Kommunikationstechnologien so genutzt werden können, dass sie dazu beitragen, die Kluft zwischen den drei Lernorten des schweizerischen Berufsbildungssystems (Berufsfachschule, Lehrbetrieb, überbetriebliche Kurse) zu reduzieren. Die zentrale Hypothese besteht darin, dass digitale Technologien nützlich sein können, um Erfahrungen am Arbeitsplatz und Unterrichtsaktivitäten miteinander zu verknüpfen.
Keywords: S 1.3.1 Ausbildung im Dualen System; L 2.1 Lernformen; L 4.2.3 Internetbasiertes Lernen / E-Learning; I 2.2.1 Westeuropa; Duales System; Kompetenzentwicklung; Kompetenzerwerb; Situiertes Lernen; Reflexives Lernen; Web 2.0; Schweiz